2013
DOI: 10.1088/1367-2630/15/8/085010
|View full text |Cite
|
Sign up to set email alerts
|

Coherent quantum transport in disordered systems: I. The influence of dephasing on the transport properties and absorption spectra on one-dimensional systems

Abstract: Excitonic transport in static-disordered one dimensional systems is studied in the presence of thermal fluctuations that are described by the Haken-Strobl-Reineker model. For short times, non-diffusive behavior is observed that can be characterized as the free-particle dynamics on the lengthscale bounded by the Anderson localized system. Over longer time scales, the environment-induced dephasing is sufficient to overcome the Anderson localization caused by the disorder and allow for transport to occur which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
175
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(185 citation statements)
references
References 57 publications
10
175
0
Order By: Relevance
“…Recently, it has been shown that the RTA becomes exact in a model for exciton transport where the inelastic scattering time is replaced by the decoherence time of the exciton. [106] The effects of short-time correlations in the dynamics of disorder have been recently studied in Ref. [107] using a stochastic model similar to Ref.…”
Section: Relaxation Time Approximationmentioning
confidence: 99%
“…Recently, it has been shown that the RTA becomes exact in a model for exciton transport where the inelastic scattering time is replaced by the decoherence time of the exciton. [106] The effects of short-time correlations in the dynamics of disorder have been recently studied in Ref. [107] using a stochastic model similar to Ref.…”
Section: Relaxation Time Approximationmentioning
confidence: 99%
“…We consider here a paradigmatic model with N twolevels systems arranged in a ring structure, which has been also analyzed in several papers [5,17,26,[30][31][32] to describe different systems, such as molecular J-aggregates [6], bio-inspired devices for photon sensing [17], and efficient light-harvesting systems [30]. In particular, it has been often considered in the frame of exciton transport in natural photosynthetic complexes, such as LHI, LHII, where chlorophyll molecules are held in a ring-like structure by a protein scaffold [33].…”
Section: The Modelmentioning
confidence: 99%
“…The interplay of dephasing (homogeneous broadening) and static disorder has also been analyzed in Refs. [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, much of recent research focused on one-dimensional nanostructures, due to their relevance to molecular aggregates, such as the J-aggregates [6], natural photosynthetic systems [7], bioengineered devices for photon sensing [8] and lightharvesting systems [9].…”
Section: Introductionmentioning
confidence: 99%